Spatio-temporal variation of the invasive copepod Oithona davisae in the zooplankton community of Kavala harbour - KOURKOUTMANI, POLYXENI; LOUFI, KATERINA; KALANTARIDOU, GEORGIA; KARAGIANNI , AIKATERINI; MICHALOUDI, EVANGELIA (Mediterranean Marine Science, 2023)
Non-indigenous species (NIS) are one of the anthropogenic effects greatly threatening biodiversity and ecosystem services. Ports and harbours are among the most susceptible environments for the arrival and establishment of these species since ballast waters represent a common pathway for NIS arrivals. However, relevant studies are limited. One of the few studies dealing with the zooplankton community of a harbour and reveals the presence of the widely distributed NIS Oithona davisae is presented in this paper, with special mention to the spatiotemporal variation of the species. The invader, O. davisae, a significant contributor to the zooplankton community, confirmed its thermophilic character and showed better development in the inner part of the harbour as well as patterns of coexistence with competing native species.